2007
DOI: 10.1111/j.1475-1313.2007.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in unselected and untreated primary open angle glaucoma patients: a pilot study

Abstract: Independent of a history and/or clinical signs of cardiovascular disease, glaucoma patients exhibit abnormal autonomic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Evaluation of ambulatory BP in patients with glaucoma can provide insight into the presence of associated modifiable vascular risk factors and ischemic risk. In the current study and consistent with previous research, 7,32,41,42 no significant differences in the average diurnal and nocturnal BP variables or the nocturnal dipping status were found between the POAG, NTG, and control groups following 24-hour BP assessment. There is, however, a lack of consistency in results reported by various groups regarding the relationship between systemic BP and glaucoma, with other studies 40,[43][44][45][46][47][48][49][50][51][52][53][54][55] finding associations between abnormal systemic BP and the presence of GON, particularly with regard to hypotension and nocturnal BP dipping.…”
Section: Commentsupporting
confidence: 80%
“…Evaluation of ambulatory BP in patients with glaucoma can provide insight into the presence of associated modifiable vascular risk factors and ischemic risk. In the current study and consistent with previous research, 7,32,41,42 no significant differences in the average diurnal and nocturnal BP variables or the nocturnal dipping status were found between the POAG, NTG, and control groups following 24-hour BP assessment. There is, however, a lack of consistency in results reported by various groups regarding the relationship between systemic BP and glaucoma, with other studies 40,[43][44][45][46][47][48][49][50][51][52][53][54][55] finding associations between abnormal systemic BP and the presence of GON, particularly with regard to hypotension and nocturnal BP dipping.…”
Section: Commentsupporting
confidence: 80%
“…20 Generally, the sympathetic system affects the vasculature in different ways. First, it may be involved in the process of atherosclerosis through platelet-derived growth factor formation and by inducing mechanical vascular wall injury as a result of increased BP and increased flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…19 Twenty-four-hour ambulatory BP, ECG monitoring, and frequency domain analysis of HRV reported that untreated POAG patients exhibit abnormal autonomic function. 20 Although there is evidence that autonomic disturbances can have circulatory implications relevant to glaucoma pathogenesis, published results are inconsistent because most of the studies have been performed in selected cases free of systemic vascular diseases such as hypertension. [13][14] Moreover, it is difficult to enroll the patients for 24 hours or 48 hours of ECG or BP measurements.…”
mentioning
confidence: 98%
“…Application of bimatoprost and travoprost resulted in an improvement in the central retinal artery blood flow in newly diagnosed open-angle glaucoma patients (Alagoz et al, 2008). An improved OBF after treatment with latanoprost was also found in patients with POAG, normal tension glaucoma and ocular hypertension (Vetrugno et al, 1998;McKibbin and Menage, 1999;Georgopoulos et al, 2002;Sponsel et al, 2002b;Erkin et al, 2004;Gherghel et al, 2008). Also, unoprostone caused an increase in OBF, a comparison of latanoprost and unoprostone revealed, that latanoprost once daily produced a OBF increase nearly twofold greater than those obtained with unoprostone twice daily (Sponsel et al, 2002a).…”
Section: Improvement Of Ocular Blood Flow By Prostaglandin F Analoguesmentioning
confidence: 94%